Loser Social Networking - Social Networking Goes to the Dogs. - Upson, S. (IEEE spectrum)
The pet industry, worth about 40 billion dollars in the United States alone, is in a growth spurt, up 65 percent since 2000. Pet products are branching out as never before in new and glamorous directions - and also in a few weird ones. A 200 dollars RFID dog tag tells owners - and their neighbors - when their pets are alive, at home, and sniffing things.